Social Media and the Service Quality of Higher Education Providers - Tamil, Chellvan (INTI International University, 2018)
This project discussesthe exploration of the usage of social media in enhancing the service quality of a Higher Education Provider. This paper reviews the trend of social media and its usage in the contemporary digital age. The discussion includes the growing prominence of social media usage for internal and external relations, such as marketing strategies, recruitments of students, life quality of students internally by using social media as peer to peer communication, and the overall service quality within the walls of the higher education provider. This research paper utilizes both quantitative and qualitative data using questionnaires and focus group interviews with college youths aged 17 to 26 with different backgrounds. The findings indicate that the background of the college youths does have significant relationship with the topic of research. This paper is a study of the growth of influence and benefits that the usage of social media brings to the service quality of higher education providers for both internal and external relations. Although there is various research regarding the usage of social media in enhancing the service quality of a Higher Education Provider, this paper focuses of the service quality (internal and external relations) that is benefited by the usage of social media in Malaysia Higher Education providers.